Pengaruh Covid 19 Dalam Penerapan Protokol Kesehatan Bagi Room Attendant Di Hotel Neo Malioboro The Effect Of Covid 19 In The Implementation Of Health Protocols For Room Attendants At Hotel Neo Malioboro - Feri Murdyantono; Lutfi Handayani; Erlina Daru Kuntari (EBBANK, 2023)
Hospitality is one of the aspects affected by the Covid-19 virus, which has caused many hotels to close due to this pandemic. Therefore the government is taking steps to implementing a comprehensive health and vaccination protocol which is supervised by CHSE as a monitoring program.This Final Project Report aims to find out the application of health protocols in the room attendant process in preparing rooms for guests at the Neo Malioboro Hotel during the Covid-19 pandemic, which complies with CHSE standards. The method of compiling this report uses descriptive qualitative methods with observation and documentation to obtain the information needed to compile this final report The result of this study is that the application of the health protocol carried out by the room attendant in the process of preparing guest rooms during the Covid-19 pandemic at the Neo Malioboro,                                                             Hotel complies with CHSE standards. In the processof cleaning rooms  during the Covid-19 pandemic, it was carried out by using PPE ( Personal Protective Equipment ) in the process of working on the room, always washing hands and using handsanitizers, using disinfectants in the room cleaning process, using safe cleaning materials, having a Covid-19 response procedure, reducing physical contact with guests or guest items, maintaining distance and employees who have been vaccinated until the final stage, all of